Preclinical Models of Multiple Sclerosis: Advantages and Limitations Towards Better Therapies - Didonna, Alessandro (Current Medicinal Chemistry, 2016)
Multiple sclerosis (MS) is a disease of the central nervous system (CNS) with an unknown etiology. MS complex pathophysiology—characterized by CNS inflammation, demyelination and axonal injury—has made its modeling in experimental systems particularly problematic. Moreover, the evidence that MS does not naturally occur in other species has further complicated MS preclinical studies. Through the years, several MS in vivo models have been developed. Experimental autoimmune encephalomyelitis (EAE) represents the most widely used MS experimental model and relies upon the autoimmune paradigm to explore MS neuropathology. Although EAE has been instrumental in understanding the molecular events which take place upon neuroinflammation, not all MS hallmarks can be efficiently shaped within this conceptual frameshift. Thus, alternative models of CNS demyelination have been characterized, either based on viral infection or neurotoxin administration. However imperfect, these models have greatly improved our knowledge of the immune system's function in health and disease. On the other side, their intrinsic distance from MS has often led to misinterpreting and overestimating the data gleaned from these experimental systems. In this review, each model will be discussed in the light of its potentiality to mimic MS and translate the most promising therapies to patients. In addition, we will address how new genomic technologies can help improve the existing models.
Keywords: cuprizone